Acoustic properties of commercially available thermal insulators − An experimental study. (15th August 2022) - Hongisto, Valtteri; Saarinen, Pekka; Alakoivu, Reijo; Hakala, Jarkko
Abstract: Thermal insulators are used structural applications, such as walls, floors, doors, roofs, duct wrappings, machine and wall linings, and vehicle envelopes. There is very little scientific comparative research about the acoustic performance of thermal insulator materials. The purpose of our study was to compare various acoustic properties of insulator materials to improve comprehensive understanding. Thirteen commercially available insulator types produced by several manufacturers were studied for thicknesses 50, 100, and 200 mm. The materials were stone wool, glass wool, cellulose, wood fiber, expanded polystyrene, polyisocyanurate, phenol foam, and cellular glass. Six acoustic quantities were measured: sound reduction index of bare insulator, sound reduction index of encapsulated insulator (insulator between two boards), sound absorption coefficient, airflow resistivity, dynamic stiffness, and reduction of impact sound pressure level in a floating floor. The acoustic performance differed significantly between insulator types for each quantity. The value range for the abovementioned six quantities for 100-mm thick insulator was extremely large: 10–27 dB, 33–52 dB, 0.20–0.78, 3.0–2700 kPa s/m 2, 1.5–730 MN/m 3, and 15–36 dB, respectively. Closed-pore materials usually carried worse acoustic properties than open-pore materials. Unexpectedly, lower thermal conductivity was associated with worse acoustic performance of two acoustic quantities. The study is the broadest acoustic investigation of thermal insulators because of the large number of studied acoustic quantities and insulator types. The study provides strong evidence that the choice of thermal insulator material plays an important role in the acoustic properties of the structural application. Manufacturers should consider declaring all six acoustic quantities to facilitate design. Highlights: Acoustic properties of thirteen thermal insulator materials were determined. The survey was exceptionally broad: six acoustic quantities were determined: Significant differences in acoustic performances were observed. Closed-pore insulators performed acoustically worse than open-pore insulators. Choice of thermal insulator has significant impact on acoustic performance.